Forensic experiments on animal scavenging: A systematic literature review on what we have and what we need - Indra, Lara; Lösch, Sandra; Errickson, David; Finaughty, Devin (Elsevier, 2023)
Vertebrate scavengers frequently affect forensic casework by feeding on human remains or by scattering body parts and bones. Therefore, animal activity can influence complete recovery of bodies, trauma analysis, and the estimation of the postmortem interval (PMI), potentially hampering identification of the deceased and elucidation of the perimortem circumstances. Experimental research is well suited to investigate scavengers and their impact on carcasses over time, generating knowledge on the forensic relevance of certain scavenger species or communities. However, there are currently no systematised standards to conduct these investigations with a forensic focus, impeding comparison and synthesis of the studies. In our work, we performed a systematic literature review and found 79 publications featuring terrestrial experiments on vertebrate scavenging and/or scattering within a forensic context. We extracted 21 variables describing the study environment, experimental design and the specimens. The results show that there is considerable inconsistency in the study designs and that some of the variables are insufficiently reported. We point out research questions and areas that require attention in future studies, stressing the importance of infrequently mentioned or applied variables. Furthermore, we recommend guidelines to include and report a list of variables in forensic scavenging and scattering experiments. These guidelines will help standardising future research in the field, facilitating inter-study consolidation of results and conclusions, and consequently, inform forensic casework.
Keywords: Scavenging; Scattering; Experimental research; Forensic taphonomy; Vertebrate scavengers; Forensic anthropology